Single Nucleotide Polymorphism and Production of IL-1β and IL-10 Cytokines in Febrile Seizures - Nur, B.G.; Sahinturk, D.; Coskun, M.; Duman, O.; Yavuzer, U.; Haspolat, S. (Neuropediatrics, 2012)
Inflammation and genetics may play a role in the pathogenesis of febrile seizures. The aim of this study was to investigate the spontaneous and lipopolysaccharide (LPS)-induced production of IL-1β and IL-10, and the association between IL-1β (−511) and IL-10 (−1082) single nucleotide polymorphisms with LPS-induced cytokine production. The study included 92 febrile seizure patients and 132 healthy controls. First, we isolated genomic DNA and by using PCR-RFLP we genotyped the individuals for the cytokines gene polymorphism. Second, peripheral mononuclear cells of the individuals were isolated and stimulated with LPS to measure secretion capacity of IL-1β and IL-10 using specific ELISA kits. We found that both the IL-1β and IL-10 production was increased in febrile seizures. The rapid increase of IL-1β production in the supernatants of the LPS-induced cells was significantly higher at the fourth and the twenty-fourth hours in febrile and complex febrile seizures, respectively. The distribution of IL-10 (−1082) G allele differs significantly between cases and controls. The IL-1β (−511) G/A and the IL-10 (−1082) G/A genotype combination was found to be higher in patients with febrile seizure. Our results showed that IL-1β and IL-10 production was not influenced by the single nucleotide polymorphisms in the pathogenesis of febrile seizures.
Keywords: febrile seizure; cytokine; polymorphism